2022
DOI: 10.1093/oso/9780197663615.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Insecure Guardians

Abstract: The police force is one of the most distrusted institutions in Pakistan, notorious for its corruption and brutality. In both colonial and post-colonial contexts, directives to confront security threats have empowered law enforcement agents, while the lack of adequate reform has upheld institutional weaknesses. This exploration of policing in Karachi, Pakistan's largest city and financial capital, reveals many colonial continuities. Both civilian and military regimes continue to ensure the suppression of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…fig. (1).The figures (2,3,4,5) showed that there are significant increasing P>0.05 in antibacterial activity specially in 50mg compared with other concentration against tested bacteria. The result also showed that there are significant increasing P>0.05 in antibacterial activity of some antibiotic such as (doxycyclin,refampin,ciprofloxacin,trimethoprim) and for this result it is used as control treatment to compare with extract .The present result showed that there is a significant P>0.05 increasing in antibacterial activity between the aqueous and alcoholic extract and some standard antibiotics in different used bacteria.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…fig. (1).The figures (2,3,4,5) showed that there are significant increasing P>0.05 in antibacterial activity specially in 50mg compared with other concentration against tested bacteria. The result also showed that there are significant increasing P>0.05 in antibacterial activity of some antibiotic such as (doxycyclin,refampin,ciprofloxacin,trimethoprim) and for this result it is used as control treatment to compare with extract .The present result showed that there is a significant P>0.05 increasing in antibacterial activity between the aqueous and alcoholic extract and some standard antibiotics in different used bacteria.…”
Section: Resultsmentioning
confidence: 82%
“…The medicinal importance of these plants is due to presence of chemical substances in them.One of these plants is Calendula officinalis, commonly known as ''potmarigold''also called Catha Officinalis, Golds, Mary Gowles,Oculus Christi,po marigold, Ruddes,it is an annual herb and belongs to Asteraceae family. (1) The plant is native to central and southern Europe,Western Asia and the US. (2) The name Calendula stems from the latin Kalendula meaning first day of the month, presumably because pot marigolds are in bloom at the start of most months of the year, The common name marigold probably refers to the Virgin Mary or its old saxon name ''ymbglidegold'' which means"it turns with the sun".…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that mesenchymal stem cell (MSC)derived extracellular vesicles exhibited therapeutic benefits in the treatment of ischemic stroke. therapeutic effects of exosomes in mice following ischemic stroke have been associated with long-term neuroprotection and enhanced angiogenesis [110,111]. The interaction between pro-apoptotic and anti-apoptotic Bcl-2 family proteins in the outer mitochondrial membrane plays an important role in neuronal cell survival [112].…”
Section: Discussionmentioning
confidence: 99%